2018
DOI: 10.1002/cctc.201801234
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight into Active Cu2+ Species Properties in One‐Pot Synthesized Cu‐SSZ‐13 Catalysts for NOx Reduction by NH3

Abstract: The Cu‐SSZ‐13 catalysts with different copper content are prepared by one‐pot method and changing the mole ratio of Cu‐tetraethylenepentamine/Al2O3. Cu‐SSZ‐13 catalyst with 3.25 wt.% Cu exhibits excellent catalytic activity (operation temperature window of 145–490 °C), adaptability to high GHSV (gas hourly space velocity) and hydrothermal stability in NH3‐SCR reaction. The results of XRD Rietveld refinement coupled with H2‐TPR and EPR show that three active Cu2+ species (Cu1, Cu2 and Cu3) locate in various sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Even the very low level of SO 2 inevitably produced from ultra‐low sulfur fuel greatly limits the applicability of the Cu‐zeolite catalysts reported so far due to their high sensitivity towards this gas [7] . For instance, the NO x conversion dropped by nearly 70 % after continuous poisoning of Cu‐SSZ‐13 zeolite with a concentration of SO 2 as low as 10 ppm for 50 h [7b] . Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Even the very low level of SO 2 inevitably produced from ultra‐low sulfur fuel greatly limits the applicability of the Cu‐zeolite catalysts reported so far due to their high sensitivity towards this gas [7] . For instance, the NO x conversion dropped by nearly 70 % after continuous poisoning of Cu‐SSZ‐13 zeolite with a concentration of SO 2 as low as 10 ppm for 50 h [7b] . Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the number of Cu 2+ on the surface follows the order Cu 0.100 -SSZ-13 > Cu 0.125 -SSZ-13 > Cu 0.075 -SSZ-13 > Cu 0.050 -SSZ-13 > Cu 0.025 -SSZ-13. Chen et al 28 reported that isolated Cu 2+ species may alleviate the NO reduction in the low-temperature region. It probably one of the reasons why the Cu 0.100 -SSZ-13 sample exhibits the best low-temperature activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the copper ions from the precursors with small anions ions like NO3 − are more accessible to enter the pore, which generates more isolated Cu Ⅱ , and exhibits excellent NH3−SCR activity. The acid sites of the molecular sieve catalyst are beneficial to adsorption and activation of NH3, which is one of the key steps for the reduction of NO by NH3 molecules [2,37]. The ammonia temperature-programmed desorption (NH3−TPD) spectra of the Cu Ⅱ −SSZ−13 catalysts are shown in Figure 4.…”
mentioning
confidence: 99%
“…Many studies have shown that the chemisorption of NH3 plays a significant role in the NH3−SCR performance [2,30,40]. The acid sites of the molecular sieve catalyst are beneficial to adsorption and activation of NH 3 , which is one of the key steps for the reduction of NO by NH 3 molecules [2,37]. The ammonia temperature-programmed desorption (NH 3 −TPD) spectra of the Cu II −SSZ−13 catalysts are shown in Figure 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation